A Hitchhiker's guide through the bio‐image analysis software universe. Issue 19 (29th July 2022) - Haase, Robert; Fazeli, Elnaz; Legland, David; Doube, Michael; Culley, Siân; Belevich, Ilya; Jokitalo, Eija; Schorb, Martin; Klemm, Anna; Tischer, Christian
Abstract : Modern research in the life sciences is unthinkable without computational methods for extracting, quantifying and visualising information derived from microscopy imaging data of biological samples. In the past decade, we observed a dramatic increase in available software packages for these purposes. As it is increasingly difficult to keep track of the number of available image analysis platforms, tool collections, components and emerging technologies, we provide a conservative overview of software that we use in daily routine and give insights into emerging new tools. We give guidance on which aspects to consider when choosing the platform that best suits the user's needs, including aspects such as image data type, skills of the team, infrastructure and community at the institute and availability of time and budget. Abstract : In this review, we provide a Hitchhiker's guide through the bio‐image analysis software universe for expert and non‐expert users.